Intrahepatic cholestasis of pregnancy: from an obstetrician point of view - Mohsen M. A. Abdelhafez; Karim A. M. Ahmed; Win Win Than; Dg Marshitah Pg Baharuddin; Fairrul Kadir; Mohammad Saffree Jeffree; Mohd Firdaus Hayati; Mohd Nazri Mohd Daud; Mohd Nazri Mohd Daud; Kai Xin Tay (Taylor & Francis Group, 2022)
Intrahepatic cholestasis of pregnancy (ICP) is the commonest among the specific dermatoses of pregnancy. The disease is characterised by intense pruritus and specifically by elevated bile acid levels and owing to the rarity of data published in this context, the disease carries a great challenge in both diagnosis and management. The disease is associated with significant maternal as well as perinatal adverse effects, hence, this article aims at improving the knowledge of the women’s health careers with the up-to-date and evidence-based, whenever possible, recommendations while managing patients with ICP.